BEM ESTAR NO TRABALHO E OTIMISMO EM ESTUDANTES TRABALHADORES - Capecce, Viviane Rosaria (2009)
The study had as general objective submit to empirical test the relationships between well-being at work and the optimism in workers students. The study used a sample chosen by convenience, consisting of 125 working students of both sexes, divided into two groups. Group 1, with 60 students at a university in São Bernardo do Campo, and group 2, with 65 young adolescents from a non-governmental organization in São Paulo. The instrument was a self-application form consists of items both dealings about variables of research and questions about personal and professional s life of participants of the study. Statistical analysis were described and multivariated. The descriptive results of the three dimensions of BET (well-being at work) show a greater presence of feelings of satisfaction with supervisors and colleagues in both groups, lower levels of satisfaction for both groups occurred with the salary and promotion factors, weak emotional bonds of group 1 with the work and the organization, lack of involvement with the work of the group 2. Both groups showed high levels of optimism, which means to say that both had a sense of future. It has been confirmed empirically the hypothesis that stock could have some association with optimism through the presence of correlation between optimism and satisfaction with colleagues and with involvement with work for the group 1. In group 2, optimism correlated with satisfaction with tasks and affective organizational commitment. This study aims to contribute to the comprehension of well-being in the workplace and optimism in their relationships in the professional context of workers students, to this way provide the better conceptual basis on the subject for scholars and to suggest actions an management practices people to enhance the well-being and promotion of human health when placed in the context of organization place.